The Effect of Independent Commissioners, Government Ownership, Company Capacity, and Profitability on Sustainability Report Disclosure - Putri, Hariana; Savitri, Enni; Diyanto, Volta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
A sustainability report is a report that provides information about the impact of a company on environmental, social, and economic aspects. With this report on sustainability report disclosure, it is expected to attract the attention of companies in global business and increase public confidence and the willingness of stakeholders to invest their capital in the company. This study aims to analyze the effect of independent commissioners, government ownership, company size, and profitability on sustainability report disclosure. In this study, 115 companies were listed on the Indonesia Stock Exchange (IDX) in 2019–2021. The sampling method used was purposive sampling. The number of samples in this study was 45 companies in 2019–2021. The analysis tool uses multiple linear regression tests. The results of this study indicate that independent commissioners have no effect on sustainability report disclosure, and company size has no effect on sustainability report disclosure. Meanwhile, government ownership affects the disclosure of sustainability reports, and profitability affects the disclosure of sustainability reports.